1995
DOI: 10.2165/00002018-199512060-00004
|View full text |Cite
|
Sign up to set email alerts
|

A Risk-Benefit Assessment of Cisapride in the Treatment of Gastrointestinal Disorders

Abstract: Cisapride is a substituted benzamide compound that stimulates motor activity in all segments of the gastrointestinal tract by enhancing the release of acetylcholine from the enteric nervous system. Cisapride is administered orally in the treatment of gastro-oesophageal reflux disease, functional dyspepsia, gastroparesis, chronic intestinal pseudo-obstruction syndromes and chronic constipation. In gastro-oesophageal reflux disease in both adults and children, cisapride provides symptomatic improvement and mucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 76 publications
3
26
1
Order By: Relevance
“…Ramosetron and the substituted benzamides cisapride and zacopride partially reversed the gastroparesis in vagotomized rats. It was reported that cisapride produced a gastroprokinetic response in both healthy men and gastroparesis patients (Wiseman and Faulds 1994;Duan et al 1995;Horowitz and Fraser 1995;Tack et al 1995). In contrast, the gastroprokinetic effects of the selective 5-HT 3 receptor antagonists ondansetron and tropisetron were weak in humans, in contrast to rats (Akkermans et al 1988;Gore et al 1990;Stacher et al 1990;Talley 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Ramosetron and the substituted benzamides cisapride and zacopride partially reversed the gastroparesis in vagotomized rats. It was reported that cisapride produced a gastroprokinetic response in both healthy men and gastroparesis patients (Wiseman and Faulds 1994;Duan et al 1995;Horowitz and Fraser 1995;Tack et al 1995). In contrast, the gastroprokinetic effects of the selective 5-HT 3 receptor antagonists ondansetron and tropisetron were weak in humans, in contrast to rats (Akkermans et al 1988;Gore et al 1990;Stacher et al 1990;Talley 1991).…”
Section: Discussionmentioning
confidence: 99%
“…5 31-33 Sumatriptan slows gastric emptying whereas cisapride and erythromycin are both gastroprokinetic drugs. [34][35][36] As the end point of the satiety test was enhanced by sumatriptan and cisapride and decreased by erythromycin, the influence of these agents matches their influence on gastric accommodation, and not their influence on gastric emptying rate. The satiety drinking test therefore offers the potential to screen for drugs that might improve impaired accommodation in a non-invasive way.…”
Section: Discussionmentioning
confidence: 99%
“…While 5-HT 4 receptor agonists are known to enhance gut contractility in humans,26 the contribution of 5-HT 4 receptors to regulating gastrointestinal motor and sensory function can only be assessed with a 5-HT 4 antagonist. In this respect, therefore, this is the first study to assess the contribution of 5-HT 4 receptors on gastrointestinal motor and sensory function in vivo in normal humans.…”
Section: Discussionmentioning
confidence: 99%
“…These are notable for interspecies and interorgan variability,5 dependence on 5-HT induced sensitisation,3 4 and/or coexistent 5-HT 3 receptor antagonism 1236 37 Cisapride, a 5-HT 4 receptor agonist with weak 5-HT 3 antagonist effects, increases upper gut contractility in humans and colonic contractility in the guinea pig, mainly by stimulating 5-HT 4 receptors on enteric neurones, leading to enhanced release of acetylcholine 26. In contrast, 5-HT acts on 5-HT 4 receptors in colonic smooth muscle to reduce the amplitude and frequency of contractions, causing relaxation 5-7.…”
Section: Discussionmentioning
confidence: 99%